Associations of Multiple Chronic Health Conditions with Health Behavior - Son, Chong-Hwan (Archives of Business Research, 2020)
This study aimed to scrutinize the association of the number of chronic health conditions with health behavior. The health behavior was measured by meeting the 2008 Physical Activity Guidelines (PAGs) for Americans for five physical activity levels for adults aged 18 years or older in the United States using data from the 2017 Behavioral Risk Factor Surveillance System (BRFSS). The empirical results of a multivariate logistic regression analysis revealed that respondents living with chronic health conditions were more likely to participate in aerobic physical activities, but not meeting the PAGs. In the insufficient physical activity subgroup, all of the predicted odds ratios were greater than one and increased as the number of chronic health conditions increased. It implied that the increase in the number of chronic conditions was positively associated with participating in insufficient physical activity. Respondents who reported having less than three chronic health conditions were more likely to meet the aerobic physical activity guidelines compared with respondents living with three or more chronic health conditions. Importantly, respondents who reported having 4 or more chronic health conditions had a higher likelihood of meeting the recommendations for muscle-strengthening activity. However, chronic health conditions would significantly discourage respondents from participating in both aerobic and muscle-strengthening physical activities. In conclusion, this study found that chronic health conditions played an important role in determining regular participation in the level of physical activity for individuals living with chronic health conditions.